Marketing Strategy for Ladaku Products at CV GEMA REJEKI Ambon - Louisa Susana Manuhutu (Jurnal Syntax Transformation, 2023)
In marketing strategy at each companies whose goal is to improve sales , then required existence of marketing and management strategies good marketing , so instruments are needed marketing consisting _ from product (product), price ( price ), place (place) and promotion ( promotion ). By In general, marketing is a social process by which individuals and groups gain what are they needs and wants by creating and exchanging products and value with other individuals and groups. And so can be said definitively that draft marketing is a philosophy business stated _ that satisfaction need consumer is condition economic and social for continuity life company . marketing so far it hasn't been missed from element competition. This research is based on back by something thinking that all organizations , whether in the form of business entities private , body of a nature public or institutions social society , have something objective its own which is motivation from its founder . Likewise with LADAKU products on CV. GEMA FORTUNE AMBON, of course it has goals , strategies and management in improving the sales . Interesting background to the research towards Ladaku Products at CV. GEMA FORTUNE Ambon is because see consumer interest _ currently in development Really encouraging although Lots competitor from other companies . However Still Many people are encouraged and interested in buying and selling LADAKU products on CV. Echo Ambon fortune. This research aims to find out mix marketing (7P) Ladaku Products at CV.Gema Ambon fortune and identify strengths , weaknesses , opportunities and threats of marketing strategies at CV.Gema Ambon fortune . The method used in this research is descriptive qualitative namely the data collected form pictures , words and not numbers . In this study , one was used tool analysis namely the SWOT method ( Strength , Weaknesses, Opportunities, Threats ). The analysis results show performance companies that can be determined by a combination internal and external factors . Hence the result of CV SWOT analysis . Echo Ambon's fortune has strengths that can be used in certain strategies as well as utilise the right opportunity in a way simultaneously so that it can be minimized or avoided existing weaknesses and threats . _ This is very profitable company by improving conditions above average ability so CV. Echo Rejeki Ambon can control existing competitors and known competitors _ _ strong . CV. Gema Fortune also deepens relationship with partners To use create good relationships as well make Attractive promotions to attract _ customer .